Universal Ethics Evaluation of ICU Patients: A Model. - Mayer, Patricia A.; McElfresh, Duncan C.; Bracamontes, Katherine (Journal of Hospital Ethics, 2022)
Background: Clinical ethics consultations are typically provided on a reactive basis and in response to ethical dilemmas or crises. Proactive clinical ethics might be preventative; however proactive ethics has primarily been demonstrated in academic settings with specific patient groups. We propose an approach in which every patient in the intensive care unit is screened for specific, actionable ethics-related criteria. Methods: Our methods were developed during a one-year pilot in which a clinical ethicist was embedded in an ICU. The ethicist evaluated as many patients as possible with no explicit selection criteria; three hundred and seventy-three patients were evaluated (39% of all admitted patients). The ethicist used four ethics-related criteria to assess patients for potentially problematic ethical issues: (a) Code Status, (b) presence/absence of Medical Power of Attorney or correctly identified Surrogate Decision Maker (c) presence/absence of Goals/Plan of Care consistent with patient wishes, and (d) presence/absence of Conflict. The time spent by the ethicist was recorded for each patient, and financial impact was evaluated separately by the institution. We retrospectively analyze these ethics-related criteria in conjunction with patient outcomes for the hospitalization. Results and Conclusions: Over two-thirds of the patients had problematic findings on initial evaluation in at least one of the four ethics criteria; 20% had no Code Status selected, 57% had no MPOA or surrogate, 49% had no clear Goals/Plan of Care and 25% had Conflict present. Of the 80% of patients with an initial Code Status, 25% were changed during the hospitalization. 22 % of the patients screened needed no ethics intervention/support, 47% received intermediate support, and 31% required extensive ethics support. Each of the four ethics-related criteria was associated with a greater need for ethics support, and each can be quickly assessed. We hope that our methods will inspire other innovations in clinical ethics consultation services.